Numerical Study of Cavitation Phenomenon in a Venturi Tube - Rachman, Muhammad Nanda Fatur; Rhakasywi, Damora; Fahrudin, Fahrudin (Journal La Multiapp, 2024)
This research aims to understand and numerically analyze the cavitation phenomenon that occurs in Venturi tubes with variations in throat length and pressure changes. This research uses Ansys Fluent 2023 R2 numerical simulation with venturi tube geometries of 25 mm, 30 mm, and 35 mm and pressures of 300,000, 600,000, and 900,000 Pa. A multiphase flow model with water liquid and water vapor is applied to predict cavitation using a mixture model. RANS steady state conditions with the k-ε turbulence model are used to solve the continuity, momentum, energy and volume fraction equations. The Schnerr-Sauer cavitation model calculates the phase transition between water-liquid and water vapor. Geometry varies by reference journal with different converging and diverging angles, outlined in tables and figures. 2D simulations are carried out using a pressure based solver with specified boundary conditions, using the Presto! for pressure solutions, and upwind and Quick schemes for discretization. The results of this research show that 1) Length throat 25 mm has the most stable distribution compared to 30 and 35 mm geometries at a pressure of 600,000 Pa. 2) The cavitation phenomenon is influenced by changes in geometry where at 35 mm geometry greater cavitation occurs in the area near the wall inlet convergent. 3) At a pressure of 900,000 Pa, the cavitation area that forms becomes larger and becomes a critical point in this journal.